2021
DOI: 10.14513/actatechjaur.00625
|View full text |Cite
|
Sign up to set email alerts
|

Material Models to Study the Effect of Fines in Sandy Soils Based on Experimental and Numerical Results

Abstract: Choosing and calibrating a robust and accurate soil material model (constitutive model) is the first important step in geotechnical numerical modelling. A less accurate model leads to poor results and more difficulty estimating true behaviour in the field. Subsequent design work is compromised and may lead to dangerous and costly mistakes. In this research, laboratory experimental results were used as a basis to evaluate several soil material models offered in Plaxis2D software. The deciding feature of the soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Balancing the sand fraction is critical in engineering applications because it improves soil performance and reduces the negative impacts of cracking in expansive soil [19]. The addition of sand to expansive soils has been extensively investigated by many researchers to determine its effect on the soil parameters [10,[20][21][22][23][24][25][26]. Previous studies have confirmed that increasing the percentage of sand increases the unconfined compressive strength (UCS) of expansive soils.…”
Section: Sand As An Additive Materials and Its Impact On Soil Parametersmentioning
confidence: 99%
“…Balancing the sand fraction is critical in engineering applications because it improves soil performance and reduces the negative impacts of cracking in expansive soil [19]. The addition of sand to expansive soils has been extensively investigated by many researchers to determine its effect on the soil parameters [10,[20][21][22][23][24][25][26]. Previous studies have confirmed that increasing the percentage of sand increases the unconfined compressive strength (UCS) of expansive soils.…”
Section: Sand As An Additive Materials and Its Impact On Soil Parametersmentioning
confidence: 99%
“…The HS model provides a wide range of defining parameters, which can be based on laboratory testing or back-calculated from field experience. It demonstrated efficiency in simulating soil behavior, encompassing both soft and stiff soils, and was extensively utilized in various research studies [61][62][63][64].…”
Section: Plaxis Validationmentioning
confidence: 99%
“…The set of parameters entered in the HS model allows the user to distinguish between loading and unloading-reloading stiffnesses. This capability enhances the model's ability to capture the soil's response more accurately to various loading conditions and its complex behavior under different stress states [64].…”
mentioning
confidence: 98%
“…The first crucial step in geotechnical numerical modeling is selecting and calibrating a robust and accurate soil material model (i.e., constitutive model). A less precise model may yield poor results and make estimating the proper behavior in the field more complex [24].…”
Section: Appropriate Constitutive Modelmentioning
confidence: 99%